Increasing Student Learning Motivation Using Project Based Learning Learning Model - Putri Anzani; Nurmairina; Nila Lestari (Journal of Practice Learning and Educational Development, 2026)
This study aims to improve student learning motivation through the implementation of the Project-Based Learning (PjBL) model in the IPAS subject for fourth-grade students at SDN 105330 Bangun Sari. The research design used in this study is Classroom Action Research (CAR). In detail, the stages in the action research design begin with planning, implementation of action, observation, and reflection in each cycle, continuing until the desired improvement is achieved. The approach used in this study is a qualitative approach. The subjects involved in the study are fourth-grade students at SDN 105330 Bangun Sari Baru, Tanjung Morawa District. The class consists of 32 students, including 9 boys and 23 girls. Based on the findings, it can be concluded that the application of the Project-Based Learning (PjBL) model can increase students' learning motivation in the IPAS subject. This is evidenced by the increase in student motivation questionnaire scores and learning test results during the learning process. Moreover, the implementation of PjBL also makes learning more meaningful and enjoyable for students, as well as actively engaging them in the learning process.